The Juridical Review for Husbands Who Do Household Abandonment - Sabrina Chaerani; Agus Sarono (Law Development Journal, 2023)
As citizens have the right to form a family and continue their generations. The State of Indonesia mandates this matter through Article 28B paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Through this article, Act No. 1 of 1974 concerning Marriage regulates various matters relating to marriage. Although everyone's hope is to create a harmonious family, a marriage can also lead to divorce. Economic reasons are the second highest reason for a divorce in Indonesia. In fact, the law has provided rules relating to the rights and obligations of each husband and wife. The research method used in this article is the normative juridical method, where a problem is studied through applicable laws such as Act No. 1 of 1974, the Compilation of Islamic Law, and Act No. 23 of 2004 concerning the Elimination of Domestic Violence.